Profiling system for skin kallikrein proteolysis applied in gene-deficient mouse models - Horn, Martin; Zbodakova, Olga; Kasparek, Petr; Srp, Jaroslav; Haneckova, Radka; Hradilek, Martin; Mares, Michael; Sedlacek, Radislav (Biological chemistry, 2018)
Kallikrein-related proteases (KLKs) play a critical role in epidermis physiology and have been implicated in skin pathologies such as Netherton syndrome. The contribution of individual KLKs to skin proteolysis is poorly understood. Monitoring of their activities in skin proteome is hampered by overlapping substrate specificities, and there is a need for novel assays. Here, we present a platform of selective and sensitive fluorogenic substrates and inhibitors for profiling KLK5, KLK7 and KLK14. These chemical tools were evaluated using recombinant KLKs and tissue from a unique set of mice deficient in eight combinations of KLKs and their natural regulator LEKTI.
Keywords: Animals; proteolýza; Proteolysis; kallikreins; inhibitors; Mice, Knockout; myši knockoutované; lidé; skin; kalikreiny; Mice; substrates; kůže; stanovení celkové genové exprese; myši; modely nemocí na zvířatech; Kallikreins; Skin; Disease Models, Animal; zvířata; mouse model; proteolysis; Gene Expression Profiling; Humans